Perlakuan Akuntansi Aktiva Tetap dan Penyajiannya dalam Laporan Keuangan Pada Toko Myhijab Cimahi - Mulyani Mulyani (Jurnal Mutiara Ilmu Akuntansi, 2024)
The purpose of this study is to determine the accounting treatment of tangible fixed assets and how they are presented in the financial statements of the Myhijab store, Accounting Treatment of tangible fixed assets and how they are presented in the financial statements in accordance with PSAK no. 16, and the impact of the implementation of PSAK no. 16 on the acquisition of profit and loss of the Myhijab store. The study was conducted using a quantitative descriptive method. Data collection techniques using interviews and documentation, then quantitative descriptive analysis was carried out. The results of the study show that the Myhijab store records the acquisition of tangible fixed assets based on the purchase price alone without taking into account other costs incurred to acquire tangible fixed assets so that the tangible fixed assets are ready for use. In accordance with PSAK no. 16, the recording of tangible fixed assets is based on their acquisition price, namely the purchase price plus the costs incurred to acquire tangible fixed assets so that the tangible fixed assets are ready for use. The impact of the implementation of PSAK no. 16 on the acquisition of profit and loss of the Myhijab store is an increase in profit in 2021 by Rp20,350,000.00.